Penerapan Model Almuqassah Sebagai Model Alternatif Kartu Kredit Syariah Di Indonesia - M Irsyad (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
This study aims to find out whether the Islamic credit cards is shariah compliant, and to find out what if al-muqassah is applied in Indonesia as an alternative model of Islamic credit cards. This study uses qualitative research methods with descriptive analysis. The object of research in this study is the Islamic credit cards model that already exists in Indonesia and the al-muqassah model. The sample in this study uses purposive sampling, namely officials from the Islamic credit card division at BNI Syariah Jakarta and DSN MUI Officials. Data Obtained from this study through interviews with relevant institutions and documentation. The results obtained from the study indicate that based on that the current Islamic Credit cards products are shariah compliant. Where the benefits provided by Islamic credit cards are in line with shariah objectives, namely maqasid dharuriyyah and maqasid hajjiyyah. However, based on the issue of shariah in the application of existing Islamic credit cards, development is still needed to improve the quality of products, especially from shariah aspects. As for the application of the al–muqassah model in Indonesia, it is very possible as long as it is supported by all parties.